A Think Piece: Setting an Agenda for Pedagogical Research and Scholarship: Key Questions for Public Administration Scholars, Practitioners, and Leaders — Why the Next Decade of Pedagogical Research and Scholarship Matters - John Diamond (Transylvanian Review of Administrative Sciences, 2022)
The period from the late 1980s to the present has been one of change and disruption at all levels of contemporary public administration. It is possible to categorize this period of change through different lenses from those of social and economic issues to those of significant political and environmental changes. At different times over the last forty years these changes have disrupted the existing institutions of government in nation states and the assumed models of governance and administration. The focus of these changes has often concentrated on the impact they have had on civil society, communities and nation states including the roles of representative governments. Less attention has been paid to the ways in which public administration pedagogues and scholars adapt to these changes and adapt their ways of working or understanding the context within which they function. This Think Piece seeks to identify what the changes have led to in terms of the pedagogical questions they raise; the issues that inform the design of the curriculum; and the implications these have for the education and training as well as the continuing professional development of practitioners and leaders of public administration.